2016
DOI: 10.3389/fnins.2016.00177
|View full text |Cite
|
Sign up to set email alerts
|

One for All? Hitting Multiple Alzheimer's Disease Targets with One Drug

Abstract: HIGHLIGHTS Many AD target combinations are being explored for multi-target drug design.New databases and models increase the potential of computational drug designLiraglutide and other antidiabetics are strong candidates for repurposing to AD.Donecopride a dual 5-HT/AChE inhibitor shows promise in pre-clinical studiesAlzheimer's Disease is a complex and multifactorial disease for which the mechanism is still not fully understood. As new insights into disease progression are discovered, new drugs must be design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 78 publications
0
57
0
Order By: Relevance
“…From the inception of amyloid cascade hypothesis to its reappraisal, it is considered to be the primary cause of this form of senile dementia [17,18]. With the advent of research and new disease progression insights, now we can assign more targets with responsibility towards either pathophysiology or associated symptoms [5]. Despite major pharma-research focused on discovering novel disease-modifying molecules, the current treatment for AD targets its affiliated symptoms only [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the inception of amyloid cascade hypothesis to its reappraisal, it is considered to be the primary cause of this form of senile dementia [17,18]. With the advent of research and new disease progression insights, now we can assign more targets with responsibility towards either pathophysiology or associated symptoms [5]. Despite major pharma-research focused on discovering novel disease-modifying molecules, the current treatment for AD targets its affiliated symptoms only [6].…”
Section: Discussionmentioning
confidence: 99%
“…Despite advanced AD researches, the current treatment strategies for AD mainly deal with providing symptomatic relief by improving cholinergic neurotransmission in CNS. Currently approved drugs for AD includes anti-cholinesterase, such as donepezil, galanthamine, and NMDA (N-methyl-D-aspartate) antagonists (memantine) [5]. At present, no disease modifying drugs are available for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…To deal the several targets of AD simultaneously, we have proposed the dual‐acting multitargeted molecules as anti‐AD agents and accordingly developed the benzofuran (donepezil component known for AChE inhibition) and coumarin (known for the AChE inhibition antioxidant and anti‐Aβ self‐aggregation)‐based hybrids to provide new class of anti‐AD molecules as shown in Figure . The coupling of these two selected pharmacophores was designed through amidic linkage of aliphatic chain and adequate length of alkyl linker was optimized through molecular docking simulations, so that designed molecules can fit comfortably in the cavity of acetylcholinesterase ( Tc AChE) enzyme and provide maximum interaction with catalytic active site (CAS) and the peripheral anionic site (PAS) to induce maximum AChE inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…3, panel A) derived from the solution structure of Ab brils 16 (pdb id:2LMN) indicated that both the 8-chloroquinazoline and the pyrido [3,2] pyrimidine templates were oriented between C-and N-terminal region whereas the C4-phenethylamine substituent was closer to the turn region Asp23-Gly29 (distance $ 6-8Å). Hydrophobic interactions were the dominating force involved.…”
Section: Inhibition Of Ab Aggregationmentioning
confidence: 99%